Chemical constituents and bioactivities of artocarpus scortechinii king. and a. hispidus f.m. jarrett - Mohd. Arriffin, Norzafneza (2018)
Two Artocarpus species from Malaysia, namely A. scortechinii King and A. hispidus F.M. Jarrett were investigated. The aims of this study were to isolate and identify the phytochemicals from different parts of these two species and also to evaluate the biological activities of the crude extracts and isolated compounds using antioxidant, a-glucosidase and anti-tyrosinase inhibition assays. Cold extractions were performed using n-hexane, dichloromethane, ethyl acetate and methanol on the stem barks and leaves of A. scortechinii to obtain the respective extracts. Extractions of A. hispidus were carried using n-hexane, dichloromethane and methanol. Fifteen compounds were isolated from these two Artocarpus species. Two new compounds together with thirteen known compounds were identified spectroscopically and by comparison with literature data. New compounds were isolated from the leaves of A. scortechinii and identified as (2R,3R)-5-hydroxy-6,7-(2,2-dimethylpyrano)-2,3-dihydroflavonol and (2R,3R)-7-hydroxy-5-methoxy-8-prenyl-2,3-dihydroflavonol together with macakurzin C, flemichapparin A, ß-sitosterol, apigenin and luteolin. 4',5-Dihydroxy-6,7-(2,2-dimethylpyrano)-2'-methoxy-8-?,?-dimethylallyflavone, stigmasterol, cudraflavone A, artocarpin, cycloartobiloxanthone, artonin E, oxyresveratrol and engelitin were obtained from the stem barks of A. scortechinii. Purification of the extracts of A. hispidus afforded four known compounds and identified spectroscopically as 4',5-dihydroxy-6,7-(2,2-dimethylpyrano)-2'-methoxy-8-?,?-dimethylallyflavone, stigmasterol, artocarpin and oxyresveratrol. Extracts from these two Artocarpus species were screened for total phenolic contents using Folin Ciocalteau’s reagent. Among all extracts tested, methanol extract of the stem barks of A. hispidus showed the highest phenolic content with TPC value of 218.93 mg GAE/g dw followed by methanol extract of the stem barks of A. scortechinii with TPC value of 136.84 mg GAE/g dw. The methanol extract of the stem barks of A. hispidus also showed the highest scavenging action among all the extracts with an IC50 value of 28.2 µg/mL towards DPPH radical. Luteolin displayed the best radical scavenging activity compared to other isolated compounds towards DPPH and ABTS radical with IC50 values of 9.51 µg/mL and 124.4 µg/mL, respectively. Luteolin also displayed the highest FRAP equivalent value of 4.07 ± 0.18 mM, which may act as good reducing agent. In a-glucosidase inhibition assay, oxyresveratrol was noticeably having strongest inhibition with an IC50 value of 3.88 µM. The methanol extract of stem barks of A. hispidus displayed the highest percentage inhibition (88.2%) in anti-tyrosinase inhibition activity followed by methanol extract of A. scortechinii (86.7%). Among the isolated compounds, oxyresveratrol exhibited the most potent tyrosinase inhibitory activity (92.3%) higher than the positive control, kojic acid (85.5%).